Rare Periampullary Carcinoma: A Case Report - Rabia Bibi, Mishal Liaqat, Kalsoom Bibi, Iram Liaqat, Yasmeen Akhtar, (Pakistan Journal of Medical & Health Sciences, 2022)
Periampullary carcinoma is usually used to define a heterogeneous group of neoplasms raised on the head of the pancreas, duodenum, and distal common bile duct. Most of the periampullary growths are adenocarcinomas. Timely diagnosis and successful surgical treatment are dependent on the first physician. A 60 years old male patient was presented to medical outpatients of Bahawal Victoria Hospital Bahawalpur in October 2019 with a rare etiology of unexpected vomiting, nausea, fatigue, weight loss, and abdominal cramps for 12 days continuously. Abdominal ultrasound revealed a hypo-echoic mass with a measurement of 2.6x2.7cm on the head of the pancreasobstructingthe distal common bile duct with mild intrahepatic cholestasis. Based on physical examination signs& symptoms and lab investigations patient was considered of having periampullary cancer and a prompt Whipple plan was prepared. The vigilance of the physician and support of the patient’s family helped to make an early decision of pancreatoduodenectomy of the patient before the multi nodulation of the tumor hence, increased the life expectancy.